Macromolecular Engineering with Tailor-made Functional Fluoropolymers via RAFT Polymerization and Diels-Alder Reaction - Ponnupandian, Siva (Curtin University, 2021)
Fluoropolymers, owing to its unique properties such as excellent water and oil resistance, chemical resistance, and thermal stability they have been widely used in developing speciality coatings. This thesis reports on the preparation of well-defined functional fluoropolymers such as block and random copolymers based on fluoroacrylates and fluoromethacrylates along with different comonomers via reversible addition-fragmentation chain-transfer (RAFT) polymerization. The potential application of these fluoropolymers mainly as a coating material along with other different properties such as self-healing behaviour was studied.